Kinerja Aparatur Desa Padangsambian Klod: Studi Deskriptif Kuantitatif di Denpasar - Suana, I Made; I G. P. Yasa; I Made Yunita (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2026)
Employee performance is a key determinant of the success of public services at the village level. This study aims to evaluate employee performance at the Village Head Office of Padangsambian Klod, West Denpasar District, Denpasar City. Using a quantitative descriptive approach, this study involved the entire employee population of 66 as respondents (total sampling). Data were collected through a questionnaire measuring 10 performance indicators: loyalty, responsibility, obedience, honesty, cooperation, initiative, understanding of duties and responsibilities, innovation, work speed, and work accuracy. The analysis results showed that the total performance score reached 2,630, which is in the interval range of 2,245 – 2,772 with a Good category. The "Initiative" indicator achieved the highest score (Very Good), while the "Obedience" and "Work Speed" indicators recorded the lowest scores although still in the Good category. These findings suggest the need to accelerate the digitalization of village bureaucracy to improve service speed amidst the transformation of the region from an agrarian to a commercial center.